Consumismo enquanto ideologia: O papel da publicidade - Brito, Nuno (2012)
Speeches convey ideology through language. The ideological function of advertising lies exactly in this point, i.e. in its symbolic character. Advertising identifies, creates and develops needs through language, offering a sense, along with the promise of happiness. In the context of liberal capitalist society, advertising is being developed as a strategy of myth production conducive to consumption.